Disaster preparedness and local governance in the Philippines - Sonny N. Domingo; Arvie Joy A. Manejar (Philippine Institute for Development Studies (PIDS), 2018)
The high level of casualties, population displacements and economic costs from recent disaster events still point to necessary augmentations in disaster preparedness. Policy has to be revisited, institutional arrangements have to be reviewed and resource mobilization issues have to be addressed. RA10121, albeit strong on its own, has to be enhanced and supported by functional department policy to be aptly cascaded. Policy and planning alignments also have to be enhanced both from the national to subnational levels and horizontally within local government institutions and national government agencies.
Keywords: 330; Disaster preparedness; local governance; disaster risk reduction and management